Category Specific Spatial Dissociations of Parallel Processes Underlying Visual Naming. (21st May 2013) - Conner, Christopher R.; Chen, Gang; Pieters, Thomas A.; Tandon, Nitin
Abstract : The constituent elements and dynamics of the networks responsible for word production are a central issue to understanding human language. Of particular interest is their dependency on lexical category, particularly the possible segregation of nouns and verbs into separate processing streams. We applied a novel mixed-effects, multilevel analysis to electrocorticographic data collected from 19 patients (1942 electrodes) to examine the activity of broadly disseminated cortical networks during the retrieval of distinct lexical categories. This approach was designed to overcome the issues of sparse sampling and individual variability inherent to invasive electrophysiology. Both noun and verb generation evoked overlapping, yet distinct nonhierarchical processes favoring ventral and dorsal visual streams, respectively. Notable differences in activity patterns were noted in Broca's area and superior lateral temporo-occipital regions (verb > noun) and in parahippocampal and fusiform cortices (noun > verb). Comparisons with functional magnetic resonance imaging (fMRI) results yielded a strong correlation of blood oxygen level-dependent signal and gamma power and an independent estimate of group size needed for fMRI studies of cognition. Our findings imply parallel, lexical category-specific processes and reconcile discrepancies between lesional and functional imaging studies.